ENGLISH TEACHER CREATIVITY IN DESIGNING ONLINE LEARNING ACTIVITIES DURING COVID-19 - Rahmayanti, Septi; Mubarok, Harir (English Edu: Journal of English Teaching and Learning, 2022)
In this pandemic situation, the learning process is replaced by online learning. Where in online learning, the teacher needs to work hard in teaching. So that online learning runs well. One way to do this in this pandemic situation is to use the teacher's creativity in making engaging online learning activities so that students can receive the material well. This study aims to determine teachers' creativity in making engaging online learning activities for English teachers in class IX at SMPN 1 Srengat. This study used a case study design with qualitative approach, and the design is used to dig deeper into teachers' creativity in making online learning activities used by English teachers. This study uses two instruments, and they are: the first instrument is interviewed, and the second instrument is documentation. The results showed that the grade IX English teacher at SMPN 1 Srengat was very creative in making online learning activities. For designing the online learning activities, the English teacher implemented four of criteria for creative teachers based on the theory of (Mulyana 2010): Fluency, Flexibility, Originality, and Elaboration. The English teacher also implements online learning activities proposed by (Jack, Chris, and Donald 2019), including Consulting, Interactive Lectures, Student presentations, Reading, and Self-Study.